ANALISIS MODEL KOMUNIKASI TRANSENDENTAL DALAM SURAT AL-FATIHAH MENURUT M QURAISH SHIHAB - Miftahul Ulum; Muhammad Mafatikhul Ilmi (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2024)
Communication as the process of conveying messages from the communicator to the communicant through media that produces effects, gives rise to questions related to communication between humans and God which cannot be seen with the naked eye. This article discusses transcendental communication, namely communication that occurs between humans and God. In this article it is argued that all elements of communication exist in communication between humans and God. The source of communication or communicator consists of God and humans. The message is in the form of Allah's verses through the Koran and prayers, remembrance that humans convey to Allah. The channel is the Al-Qur'an, one of which is in Surah Al-Fatihah, which functions as a channel for God's messages and an intra-personal channel. The recipient or communicant is basically the same as the source or communicator. The expected effect and feedback in this transcendental communication is that humans must carry out what is ordered and stay away from what is prohibited. The effect can also be in the form of the servant's prayer being answered, inner peace, or being able to occupy heaven in the afterlife. Meanwhile, communication models that can be in line with the transcendental communication process are the Stimulus Response (S-R) Model, the Aristotelian Model, and the Lasswell Model